Low serum fatty acid levels in pregnancies with fetal gastroschisis: A prospective study. Issue 4 (25th March 2018) - Centofanti, Sandra F.; Francisco, Rossana P. V.; Phillippi, Sonia T.; Castro, Inar A.; Hoshida, Mara S.; Curi, Rui; Brizot, Maria L.
Abstract : Fetal gastroschisis is a paraumbilical abdominal wall defect with herniation of abdominal organs. The underlying cause of the disease remains unknown; however, studies suggest that nutritional factors may play a role in its development. This prospective case‐control study explored the association of serum fatty acid levels of pregnant women and occurrence of gastroschisis. Gastroschisis group comprised 57 pregnant women with fetuses with gastroschisis, and the control group comprised 114 pregnant women with normal fetuses. Serum fatty acids levels were compared between the groups for the overall pregnancy at <34 weeks; ≤25 weeks, and >25 and <34 weeks; and at delivery. Total fatty acids ( p  = .008), unsaturated fatty acids ( p  = .002), and the C18:1n9/C18:00 ratio ( p  = .021) were lower in the gastroschisis group than in the control group during the overall pregnancy; however, the C16:00/C18:2n6 ratio ( p  = .018) was higher in the gastroschisis group than in the control group during the same period. Total fatty acids ( p  = .044) and unsaturated fatty acids ( p  = .024) were lower in the gastroschisis group at ≤25 weeks, and unsaturated fatty acid ( p  = .025) and the C18:1n9/C18:00 ratio ( p  = .013) were lower in the gastroschisis group than in the control group at >25 and <34 weeks. Pregnant women with fetuses with gastroschisis have low serum fatty acids levels during pregnancy. These findings suggest that fatty acids levels may be involved in the pathogenesis of fetal gastroschisis.